Papers of the International Advanced Technology Forum : frontiers of knowledge for industrial excellence, 7-8 Nov. 2000, Kuala Lumpur - International Advanced Technology Forum (2000 : Kuala Lumpur); Universiti Putra Malaysia ([S.l. : s.n.], 2000)
28